Combined Earthquake-Wave Effects on the Dynamic Response of Long-Span Cable-Stayed Bridges - Xinhu Tang; Peng Chen (Advances in Civil Engineering)
In order to investigate the dynamic response of a deep-water long-span cable-stayed bridge under the combined action of earthquakes and waves, this paper establishes a model of a certain deep-water long-span cable-stayed bridge based on the finite element method. According to the corresponding theoretical models, the equivalent added mass caused by internal and external water during earthquake actions and wave forces were calculated. A comparative analysis of the dynamic responses under only earthquake actions, only wave actions, and the combined actions of earthquakes and waves were conducted. The results indicate that the presence of water increases the dynamic response of the structure under earthquake actions, with the maximum increase in structural shear force reaching 71.57%. Under lateral earthquake actions, the impact of hydrodynamic forces on the dynamic response of the structure increases with the depth of water, reaching its maximum increase at a water depth of 40 m. Under longitudinal earthquake actions, the impact of hydrodynamic forces on the dynamic response of the main tower also shows a trend of increasing with the depth of water. However, for the auxiliary piers, their shear force and bending moment show a trend of first increasing and then decreasing. As the water depth increases from 29 to 40 m, the impact rates of their shear force and bending moment decrease by 35.12% and 11.71%, respectively. The increase in wave height will cause an increase in the dynamic response of the structure, but it will not change the period of the response time-history curve. Furthermore, the increase in wavelength not only causes an increase in the dynamic response of the structure but also leads to an increase in the period of the response time-history curve. Compared to the solitary action of earthquakes, the increase in the amplitude of the internal force response of the main tower and auxiliary piers under the combined action is about 10%–12%, indicating that the impact of wave action on the dynamic response of the structure cannot be ignored, but earthquake action still dominates.